Expected Salary Premium for a Home Office – A Survey of Accounting and Controlling Students - Bartosz KUREK (Communications of International Proceedings, 2021)
Recent COVID-19 pandemic commenced a change in working habits among white-collar professionals. Home office became a new workplace for employees in a finance sector. Employees recognize drawbacks of home office and these outweigh its benefits. To balance advantages with disadvantages professionals require an increase in salary level. By conducting an anonymous survey among Accounting and Controlling full-time master students at Cracow University of Economics a required premium for performing professional obligations from home is identified. It is statistically significant and equals 128 PLN for a graduate without professional experience and 98 PLN for a graduate with three years of professional experience.
Keywords: Salary Expectations; COVID-19; Human Capital; Return on Human Capital.